REGENERASI IN VITRO PLANLET JAHE BEBAS PENYAKIT LAYU BAKTERI PADA BEBERAPA TARAF KONSENTRASI 6-BENZYL AMINO PURINE (BAP) DAN 1-NAPHTHALENE ACETIC ACID (NAA) - Marlin Marlin (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
The objective of this experiment was to determine the optimum concentration of 6- benzyl amino purine (BAP) and 1-naphthalene acetic acid (NAA) for in vitro regeneration of diseases-free plantlets of ginger. Meristem part of ginger rhizome selected from infected area was used as plant material. The explant was cut into 0.5 cm3 and, then, cultured in an MS basal medium supplemented with combination of treatments. The experiment wasarranged in Completed Randomized Design with factorial arrangement of the treatments. The first factor was BAP concentrations (0,1,2,3,4 and 5 ppm of BAP), and the second factor was NAA concentrations (0,1,2,3,4 and 5 ppm of NAA). The experiment was done in 18 sterilization methods and planting techniques to regenerate disease-free plantlets. The results showed that supplements of BAP and NAA affectedin vitro plantlet regeneration of ginger. Additional BAP and NAA on the basal media improved percentage of root, shoot and plantlet formation about 83.33- 100%. The highest number of shoot was obtained on 4 ppm of BAP and 3 ppm of NAA, while the highest number of root was obtained on media with addition 3.58 ppm of BAP and 5 ppm of NAA. Supplementing the medium with 3-4 ppm of BAP and 3 ppm of NAA was the best combination for regenerating plantlets of ginger. Microscopic test of micro-rhizome cell showed that there was only 2% of sample infected by P. solanacearum. This result indicated that in vitro technique could be used as an alternative method to produce a disease-free rhizome of ginger.